Study on the seismic control measure of the underground large-scale frame structure. (June 2022) - Qiu, Dapeng; Chen, Jianyun; Cao, Xiangyu
Abstract: The seismic control measures with isolation bearings (SMIB) on top column joints are widely employed in underground frame structures with small cross-sections. This paper reveals the seismic control mechanism of the SMIB, and verifies the applicability of the SMIB for the underground large-scale frame structure (ULSFS). It is found that: the stresses of middle columns in the ULSFS would be controlled to some extent, but the seismic responses of floor slabs and outside walls would increase due to the smaller lateral horizontal resistance after the SMIB. The SMIB can not aim at the failure mechanism of the ULSFS, and it has been demonstrated to be ineffective for the ULSFS. Therefore, an innovative separation seismic control measure (SSCM) is proposed for the ULSFS based on the structural seismic characteristics and failure mechanisms. The fixed beam-column joints in the frame structure are released to be hinged, and the energy dissipation devices are added between the internal frame structure with outside walls. The analysis results show that the SSCM would cut down the adverse effects of the considerable soil structure interaction and decrease the seismic responses of the whole ULSLS efficiently. The seismic reduction ratio also demonstrates the SSCM has highly reliable seismic control effects on both the entire structure and vulnerable positions.